Diseño, Construcción e Implementación de un Banco de Prácticas de Laboratorio Mediante Uso de Arduino para la Carrera de Ingeniería Electromecánica - Delgado Tapia, Jeffry Vicente (2019)
The present work is focused to design, construction and implementation of a laboratory practice bench for the electromechanical engineering career of UNL, based on Arduino. In the first instance, the topics studied in the study’s plan of the career are analyzed to propose a series of different complexity practices, each of these practices are carried out in protoboard to determine its functionality, necessary materials, programming code and connections to peripherals from Arduino card. Then, the Bluetooth application for each practice is developed using the MIT APP INVENTOR platform to facilitate the practices execution. The proposal to the different practices is the product of a topics addressed analysis in the curriculum from career, where the use of Arduino is convenient and precise for execution of activities related to electronics, programming, control, and automation; important in the electromechanical professional training. Each of the practices are made on protoboard for connecting the peripherals of the electronic card to determine its functionality, required materials, programming code and connections of peripherals to Arduino Mega 2560 electronic card. Then, the programming line and interface of the Bluetooth application for each practice are developed through the MIT APP INVENTOR platform. A manual is prepared with the object that the student, laboratory technician or teacher knows in detail the operation of each practice and can execute it. Also, there is a format that accompanies the practice bench to show the connection diagram, materials to use, recommendations to consider and the QR code to download the .APK extension file of the application to use for each practice. Finally, the use of the bank prepared is validated with students from career, where the contribution about the same to the professional training, the degree of difficulty of the practices, the ergonomics of the bank and disposition of elements and the use of the practice manual are evaluated.